The Influence of Social Media on the Development of Adolescent Language and Character from an Islamic Perspective - Abdurrozak Abdurrozak (Cipta Pustaka Nusantara, 2026)
This study investigates the influence of social media on adolescent language use and character development from an Islamic perspective, addressing a critical gap in existing research that often examines digital communication without integrating linguistic analysis and Islamic ethical frameworks. While prior studies have explored the impact of social media on youth behavior, limited attention has been given to how language practices in digital spaces reflect and shape moral values within an Islamic context. This research aims to analyze patterns of language use among adolescents on social media and to examine their implications for character formation in relation to Islamic principles of ethical communication. A qualitative descriptive method was employed, involving observation of adolescents’ online interactions, documentation of digital discourse, and analysis of relevant scholarly literature. The findings indicate that social media promotes the widespread use of informal language forms, such as slang, abbreviations, and code-mixing, which may influence adolescents’ formal language competence. More importantly, these linguistic practices are closely linked to shifts in communication ethics, including reduced politeness, impulsive expression, and the pursuit of social validation. From an Islamic perspective, such tendencies may contradict core values such as akhlaq (moral conduct), adab (proper manners), and responsibility in speech. This study contributes to both linguistic and Islamic studies by offering an integrated analysis of language behavior and moral development in digital contexts. It emphasizes the need for value-based guidance from families, educational institutions, and society to foster ethical and responsible communication among adolescents in the digital era.